2004
DOI: 10.1165/rcmb.2003-0127oc
|View full text |Cite
|
Sign up to set email alerts
|

A Common Pathway for the Uptake of Surfactant Lipids by Alveolar Cells

Abstract: The uptake of different surfactant lipids-dipalmitoylphosphatidylcholine (DPPC), phosphatidylglycerol (PG), or phosphatidylinositol (PI)-and liposomes with a surfactant-like composition by alveolar type II cells (alveolar type II cells) and macrophages (alveolar macrophages) was studied in vitro. Fluorescent-labeled liposomes containing either 86% of the studied lipid, i.e., DPPC, PG, PI, and 6% labeled phosphatidylethanolamine (PE) and 8% cholesterol or a lipid mixture similar to surfactant (DPPC, PG, PI, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
7
29
0
1
Order By: Relevance
“…Moreover, expression of the M2 marker Ym1 ( Figure 5B) and the lipid receptor/ transporter genes (Cd36, Sra-1, Lxr-a, Abca1, and Abcg1; see Figures E3A and E3B) were increased in macrophages from the bleomycin-injured lung. No differences in expression of the M1 marker Tnf-a were observed in macrophages from control and bleomycin-injured lungs, further suggesting a shift toward an M2 or "reparative" macrophage phenotype (25,26) that favors collagen deposition and fibrosis.…”
Section: Foam Cell Formation Induces the Production Of Tgf-b1mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, expression of the M2 marker Ym1 ( Figure 5B) and the lipid receptor/ transporter genes (Cd36, Sra-1, Lxr-a, Abca1, and Abcg1; see Figures E3A and E3B) were increased in macrophages from the bleomycin-injured lung. No differences in expression of the M1 marker Tnf-a were observed in macrophages from control and bleomycin-injured lungs, further suggesting a shift toward an M2 or "reparative" macrophage phenotype (25,26) that favors collagen deposition and fibrosis.…”
Section: Foam Cell Formation Induces the Production Of Tgf-b1mentioning
confidence: 89%
“…The uptake of liposomes was performed as described previously (25). Details are provided in the online supplement.…”
Section: Measurement Of Liposome Uptake By Atii Cellsmentioning
confidence: 99%
“…Alveolar type II epithelial cells produce and secrete pulmonary surfactant, a phospholipid-rich material lining the inside of the alveolar cells, and old surfactant is cleared from the alveolar space by alveolar type II epithelial cells and alveolar macrophages for degradation 36 . Inorganic phosphate released from the degraded phospholipids is transported from the alveolar space by the type IIb sodium-phosphate cotransporter, which is primarily expressed in alveolar type II epithelial cells 37 . This metabolism of pulmonary surfactant and inorganic phosphate in the alveolar space suggests that calcium phosphate may be more likely to be precipitated under conditions of alveolar type II epithelial cell damage, and calcium phosphate precipitate is bound by alendronate and then efficiently phagocytosed by alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…PG is the second major component after phosphatidylcholine, and in vitro studies have demonstrated a significant effect of PG on the uptake (25,27). However, extrapolation of the results of in vitro experiments on the uptake of liposomes to the in vivo situation is not always valid; our group has already demonstrated significant differences when comparing in vivo and in vitro uptake of surfactant-like liposomes (26).…”
mentioning
confidence: 86%
“…Especially SP-A is known to affect the uptake of surfactant by alveolar cells (1,14,15,33). However, in vitro studies have demonstrated that, apart from these SPs, the different lipid components also affect the uptake (25,27). Significant differences in lipid composition between adults and neonates have been described (2,(11)(12)(13).…”
mentioning
confidence: 99%